CTX-M-15-non-ST131 Escherichia coli isolates are mainly responsible of faecal carriage with ESBL-producing Enterobacteriaceae in travellers, immigrants and those visiting friends and relatives. (March 2015) - Valverde, A.; Turrientes, M.-C.; Norman, F.; San Martín, E.; Moreno, L.; Pérez-Molina, J.A.; López-Vélez, R.; Cantón, R.
Abstract: Prevalence of extended-spectrum β-lactamases (ESBL) and/or carbapenemase-producing Enterobacteriaceae (EPE and CPE) in stool samples from 75 travellers, 8 people visiting friends and relatives and 3 immigrants who had travelled or came from tropical or subtropical areas was determined. Thirty-one per cent (27/86) of the subjects were faecal carriers of EPE, and 37 EPE isolates were recovered (36 Escherichia coli, 1 Klebsiella pneumoniae ). CTX-M-15 was the most prevalent enzyme (64.8%) mainly associated with E. coli belonging to phylogroup A and sequence type complex 10. Most of the ESBL-positive travellers (50%) had visited countries from Asia.